The poling thrust in ski skating is accomplished by hip and knee flexion in v2 but not in v1 - Hallén, J.; Myklebust, H.; Losnegard, T. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Introduction: Ski skating is a complex cyclic technique where both arms and legs are producing the propulsive forces. The main ski skating techniques are V1 and V2. Smith et al. (2009) showed that the leg/ski thrust in V1 and the arm/poling thrust in V2 contributed most to the propulsion. The present study will evaluate how lowering of the center of mass (COM), contribute to the poling thrust during V1 and V2 skate, evaluated by accelerometry. Methods: Fourteen elite senior male cross country skiers (VO2max: 76.2 (4.8) ml/kg/min) volunteered and were all familiar with rollerski treadmill testing. After a warm up, the skiers did two 1-min trials with V1 and V2 skate at 4° inclination and 3 m/s. One tri-axial accelerometer (pluX, Lisbon, Portugal) was mounted directly to the skin at the subject`s lower back (hip). Hip displacement was calculated by double integration of the signal. Uniaxial accelerometers were attached to the poles and the ski-boots to detect poles and skis hits and lift-offs. Results: The hip vertical displacement was 50% larger in V2 than V1 [0.12 (SD 0.02) vs 0.08 (0.02) m, p<0.05] even if the pattern of acceleration was similar. However, in the horizontal direction (for-aft), the patterns were different between techniques and maximal forward acceleration was 28% larger in V2 than V1 [3.7 (0.4) vs 2.9 (0.6) m/s^2, p<0.01]. During V2, forward acceleration was linked to the pole thrust and lowering of the hip, while the largest forward acceleration in V1 occurs without pole ground contact. Furthermore, in V1 the hip was elevated during the poling thrust. Discussion Displacement of the hip in the vertical direction approximates change in the skier`s potential energy. Hip acceleration in forward direction approximates the size of the propulsive forces. The present results indicate that the potential energy gained by extension of hip and knee joints during the first part of the ski thrust, is transferred to forward kinetic energy by the poling action in V2. Video analysis reveals that during the first 75% of the poling action in V2, only minor changes occur in the angles of the shoulder and the elbow joints. Hence, the poling action is actively performed by knee- and hip flexion more than dynamic action of the arm muscles. Contrary to V2, the reaction forces through the poles are partly used to elevate the hip in V1. Conclusion: The present data shows that the poling thrust in V2 is accomplished to a large extent by the legs and trunk by first elevating the COM to gain potential energy before lowering COM by gravity and actively flexion of the hip and the knees during the pole thrust.